2018
DOI: 10.1101/369249
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CRISPR-Cas9 human gene replacement and phenomic characterization inCaenorhabditis elegansto understand the functional conservation of human genes and decipher variants of uncertain significance

Abstract: Our ability to sequence genomes has vastly surpassed our ability to interpret the genetic variation we discover. This presents a major challenge in the clinical setting, where the recent application of whole exome and whole genome sequencing has uncovered thousands of genetic variants of uncertain significance. Here, we present a strategy for targeted human gene replacement and phenomic characterization based on CRISPR-Cas9 genome engineering in the genetic model organism Caenorhabditis elegans that will facil… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 122 publications
0
16
0
Order By: Relevance
“…However, the challenge currently lies in inserting larger fragments of DNA, such as the integration of fluorescent reporters into endogenous loci or gene replacements. Even though it has been demonstrated that this can be achieved by using targeting vectors with long homology arms (Dickinson et al 2013;Schwartz and Jorgensen 2016;McDiarmid et al 2018), plasmid construction usually involves cumbersome cloning steps. An alternative option is to use a PCR product with 35-bp flanking sites that are homologous to the insertion site as a repair template (Paix et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, the challenge currently lies in inserting larger fragments of DNA, such as the integration of fluorescent reporters into endogenous loci or gene replacements. Even though it has been demonstrated that this can be achieved by using targeting vectors with long homology arms (Dickinson et al 2013;Schwartz and Jorgensen 2016;McDiarmid et al 2018), plasmid construction usually involves cumbersome cloning steps. An alternative option is to use a PCR product with 35-bp flanking sites that are homologous to the insertion site as a repair template (Paix et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Our data adds to the recent and rapidly expanding use of model organism phenomics to discover the functions of poorly characterized genes identified through genomic sequencing. 44,101,[153][154][155][156][157][158] We have shown how such data can be used to identify novel genetic interactions, establish variant functional assays, and develop tests of phenotypic reversibility.…”
Section: Discussionmentioning
confidence: 99%
“…49,141 We have also recently shown that directly replacing daf-18 with only a single copy of its human ASD-associated ortholog PTEN at the endogenous locus using CRISPR-Cas9 is able to rescue multiple sensory abnormalities caused by complete deletion of daf-18. 142 A recent systematic humanization effort of 414 genes in yeast showed that >50% of human genes could functionally replace their yeast ortholog. 143 Indeed, at this point it would not be surprising if a highly conserved human gene could replace its C. elegans ortholog.…”
Section: Asd-associated Genes Are Continuously Distributed In Phenotymentioning
confidence: 99%
See 2 more Smart Citations